A high heat-resistant meta-aramid fiber and its preparation method and application
By modifying the molecular chain of the meta-aramid fibrid fiber with a fluorenyl group and introducing a fluorenyl group, the problem of the existing technology that the meta-aramid fibrid fiber is prone to aging during high-temperature treatment is solved, and high heat resistance is achieved. and stability improvement.
Patent Information
- Application Number
- CN202411554590.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing meta-aramid aramid precipitation fibers are prone to thermal oxygen aging during high-temperature hot pressing, resulting in yellowing and mechanical properties degradation. The existing heat-resistant additives have low utilization rate and poor compatibility, making it easy to block the equipment.
By modifying the molecular chain with fluorenyl groups and introducing fluorenyl groups, the heat resistance of the fibrid fiber is improved. The fluorene structure-containing phenylenediamine monomer is polymerized with m-phenylenediamine and isophthaloyl chloride to form High heat-resistant meta-aramid polymer, and high heat-resistant meta-aramid fibrids are obtained through a precipitation molding process.
The heat resistance stability of the fibrid fiber is improved, other characteristics are maintained, the heat loss resistance of downstream products is improved, and the heat resistance and whiteness are improved.
Smart Images

Figure SMS_4 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to a highly heat-resistant meta-aramid fibrid and a preparation method and application thereof, belonging to the technical field of meta-aramid fibrid. Background Art
[0002] Aramid 1313 precipitated fibrils (MAF), as a differentiated product of meta-aramid fiber, is a special fiber with excellent comprehensive properties. This product has excellent properties such as friction resistance, high degree of fibrillation, low static electricity, dimensional stability, high strength, high modulus and good dispersibility. It is widely used in electrical insulating paper, high-temperature filter materials, protective clothing, honeycomb structure materials, etc. It is an important basic material in high-tech fields such as aerospace, aviation, national defense, electronics, communications, environmental protection, petroleum, chemical industry, and marine development.
[0003] MAF inherently has good high temperature resistance, but currently in the process of processing MAF into aramid paper, in order to increase the density of the paper sheet, form a dense structure, and improve the mechanical strength of the paper sheet, a high-temperature hot pressing process is required. However, under this treatment condition, meta-aramid paper is prone to thermal oxidation aging, yellowing, and decreased mechanical properties.
[0004] In the prior art, in order to improve the heat resistance of fibrids, halogen compounds are usually directly added in the papermaking process to improve the heat resistance of aramid paper, but the loss of this series of additives is large and the utilization rate is low. There are also inorganic additives added to the polymer solution, for example, Chinese patent application CN113789583A discloses an anti-yellowing meta-aramid fibrid and its preparation method and application, which is to add inorganic additive bismuth hydroxide to the polymer solution to prevent yellowing and thermal oxidation of paper; but the inorganic additive has poor compatibility with the polymer, poor mixing uniformity, and is easy to form sedimentation in the production process. The aggregated granular additives in the production process are easy to block the equipment and are easy to precipitate in the subsequent washing process, so the utilization rate is low. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a highly heat-resistant meta-aramid fibrid and a preparation method and application thereof, wherein the heat resistance of the fibrid is improved by modifying the molecular chain with a fluorene group. The meta-aramid fibrid has heat-resistant stability and does not change other properties of the fibrid itself, and is suitable for obtaining the highly heat-resistant meta-aramid fibrid through a precipitation molding process.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a highly heat-resistant meta-aramid fiber, wherein the meta-aramid fiber contains at least one of the following structural polymers:
[0007] ;
[0008] The number average molecular weight of the meta-aramid fibrid is 150,000-220,000.
[0009] The present invention also discloses a method for preparing highly heat-resistant meta-aramid fibrid, the preparation method comprising:
[0010] S1, m-phenylenediamine and isophthaloyl chloride are polymerized to obtain an initial polymerization solution;
[0011] S2, mixing another portion of isophthaloyl chloride and the fluorene structure-containing phenylenediamine monomer to obtain a mixture, adding the mixture to the initial polymerization solution in step S1 to react, and after the reaction is completed, adjusting the pH to a weak alkaline state to obtain a highly heat-resistant meta-aramid polymer;
[0012] S3. The high heat resistant meta-aramid polymer is subjected to a precipitation molding process to obtain the high heat resistant meta-aramid precipitated fiber.
[0013] Furthermore, the phenylenediamine monomer containing a fluorene structure is any one of 2,7-diaminofluorene, 2.7-bis(3-aminophenyl)fluorene, and 9.9-dimethyl-2.7-bis(3-aminophenyl)fluorene.
[0014] Further, the molar ratio of the amount of m-phenylenediamine used in step S1 to the total amount of isophthaloyl chloride used in steps S1 and S2 is 1:(0.80-1.00);
[0015] The molar ratio of the amount of the fluorene structure-containing phenylenediamine monomer used in step S2 to the amount of the m-phenylenediamine used in step S1 is (0.001-0.0025): 1;
[0016] The amount of isophthaloyl chloride used in step S2 is 5% to 25% of the total mass of isophthaloyl chloride in steps S1 and S2.
[0017] Furthermore, the polymerization reaction process in step S1 is: under the protection of inert gas, m-phenylenediamine is dissolved in a polar solvent, and then the isophthaloyl chloride is added, and the reaction temperature is controlled to be 5-25° C.;
[0018] In step S2, the reaction is carried out under the protection of an inert gas, and the reaction temperature is controlled at 20-40°C.
[0019] Furthermore, in step S1, the addition rate of isophthaloyl chloride is 30-45 kg / h; in step S2, the addition rate of the mixture of isophthaloyl chloride and fluorene-containing phenylenediamine monomer is 5-15 kg / h.
[0020] Furthermore, the mass concentration of the highly heat-resistant meta-aramid polymer is 15-20wt%, the viscosity at 25°C is 50-200 Po, and the polymer pH is 8-10.
[0021] Furthermore, the precipitation molding process is: the high heat resistant meta-aramid polymer is diluted with DMAC to obtain a polymer dilution solution with a mass concentration of 7-10wt%, the polymer dilution solution and the DMAC aqueous solution are transported to a precipitator for high-speed shearing, and then countercurrent washing is performed to obtain the high heat resistant meta-aramid precipitated fiber.
[0022] Furthermore, the mass ratio of the high heat-resistant meta-aramid polymer to the DMAC aqueous solution is 1:(7-9), the mass concentration of DMAC in the DMAC aqueous solution is 25-45%; the high-speed shearing speed is 5000-8000rpm, and the stock solution gun diameter is 0.04-0.06mm.
[0023] The invention also discloses an application of high heat-resistant meta-aramid fibrid, and the high heat-resistant meta-aramid fibrid is applied to aramid paper.
[0024] The beneficial effects of the present invention are:
[0025] The highly heat-resistant meta-aramid fibrid of the present invention is based on the original meta-aramid, and through the third monomer modification technology, the molecular chain contains a fluorenyl group, thereby realizing the modification of the molecular structure without changing the characteristics of the meta-aramid fibrid itself, so that the fibrid made using the modified meta-aramid polymer has higher heat stability during the production process, providing raw materials with better performance for downstream product applications, and improving the heat loss resistance of downstream products.
[0026] In addition, the fluorene-based compounds have excellent properties such as good dielectric properties, mechanical properties, chemical resistance, and moisture and heat resistance. The introduction of fluorene-based groups into polymer molecular chains can effectively improve the heat resistance of the polymer. At the same time, the fluorene structure is grafted into the polymer molecular chain in the form of a covalent bond, and will not cause functional attenuation due to the preparation process. In the preparation method described in the present invention, by introducing fluorene-based groups into the polymer molecular chain and combining appropriate precipitation molding process conditions, the high heat-resistant meta-aramid precipitated fibers finally obtained have good heat resistance and good whiteness. DETAILED DESCRIPTION
[0027] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0029] A highly heat-resistant meta-aramid fibrid, wherein the meta-aramid fibrid contains at least one of the following structural polymers:
[0030] ;
[0031] The number average molecular weight of the meta-aramid fibrid is 150,000-220,000, wherein n in the above structural formula is a natural number greater than 0, representing a repeating unit structure in the polymer.
[0032] A method for preparing highly heat-resistant meta-aramid fibrid, the preparation method comprising:
[0033] S1, m-phenylenediamine and isophthaloyl chloride are polymerized to obtain an initial polymerization solution;
[0034] S2, mixing another portion of isophthaloyl chloride and the fluorene structure-containing phenylenediamine monomer to obtain a mixture, adding the mixture to the initial polymerization solution in step S1 to react, and after the reaction is completed, adjusting the pH to a weak alkaline state to obtain a highly heat-resistant meta-aramid polymer;
[0035] S3. The high heat resistant meta-aramid polymer is subjected to a precipitation molding process to obtain the high heat resistant meta-aramid precipitated fiber.
[0036] Specifically, the phenylenediamine monomer containing a fluorene structure is any one of 2,7-diaminofluorene, 2.7-bis(3-aminophenyl)fluorene, and 9.9-dimethyl-2.7-bis(3-aminophenyl)fluorene; the structural formula of the phenylenediamine monomer containing a fluorene structure is as follows:
[0037] .
[0038] Specifically, the molar ratio of the amount of m-phenylenediamine used in step S1 to the total amount of isophthaloyl chloride used in steps S1 and S2 is 1:(0.80-1.00);
[0039] The molar ratio of the amount of the fluorene structure-containing phenylenediamine monomer used in step S2 to the amount of the m-phenylenediamine used in step S1 is (0.001-0.0025): 1;
[0040] The amount of isophthaloyl chloride used in step S2 is 5% to 25% of the total mass of isophthaloyl chloride in steps S1 and S2.
[0041] Specifically, the polymerization reaction process in step S1 is: under the protection of inert gas, m-phenylenediamine is dissolved in a polar solvent, and then the isophthaloyl chloride is added, and the reaction temperature is controlled to be 5-25° C.;
[0042] In step S2, the reaction is carried out under the protection of an inert gas, and the reaction temperature is controlled at 20-40°C.
[0043] Specifically, the polar solvent is dimethylformamide, dimethylacetamide or N-methylpyrrolidone.
[0044] Preferably, the polar solvent is dimethylacetamide or N-methylpyrrolidone. Compared with dimethylformamide, dimethylacetamide has higher thermal stability and hydrolysis stability, and lower corrosiveness and toxicity. Therefore, the use of dimethylacetamide is better than dimethylformamide.
[0045] Specifically, in step S1, the addition rate of isophthaloyl chloride is 30-45 kg / h; in step S2, the addition rate of the mixture of isophthaloyl chloride and fluorene structure-containing phenylenediamine monomer is 5-15 kg / h.
[0046] Specifically, in step S2, the substance used to adjust the pH is any one of alkaline earth metal hydroxides or organic amines.
[0047] More specifically, the alkaline earth metal hydroxide is sodium hydroxide or calcium hydroxide.
[0048] Specifically, the mass concentration of the highly heat-resistant meta-aramid polymer is 15-20wt%, the viscosity at 25°C is 50-200 Po, the polymer pH is 8-10, and the polymer solution is diluted.
[0049] Specifically, the precipitation molding process is: the high heat-resistant meta-aramid polymer is diluted with DMAC to obtain a polymer dilution liquid with a mass concentration of 7-10wt% (the viscosity of the polymer dilution liquid at 25°C is 90-110CP), the polymer dilution liquid and the DMAC aqueous solution are transported to a precipitator for high-speed shearing, and then countercurrent washing is performed to obtain the high heat-resistant meta-aramid precipitated fibers.
[0050] Specifically, the mass ratio of the high heat-resistant meta-aramid polymer to the DMAC aqueous solution is 1:(7-9), the mass concentration of DMAC in the DMAC aqueous solution is 25-45%; the speed of the high-speed shear is 5000-8000rpm, and the diameter of the stock solution gun is 0.04-0.06mm.
[0051] An application of highly heat-resistant meta-aramid fibrid, wherein the highly heat-resistant meta-aramid fibrid is applied to aramid paper.
[0052] The following is a specific example of preparing highly heat-resistant meta-aramid fibrids, wherein the amounts of the various raw materials used in the examples are all molar amounts.
[0053] Example 1
[0054] (1) 2 parts of m-phenylenediamine were added to 30 parts of dimethylacetamide, the temperature in the system was controlled to be 25°C, and 1.6 parts of isophthaloyl chloride were added under nitrogen protection to carry out polymerization reaction to obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride was 30 kg / h;
[0055] (2) 0.4 parts of isophthaloyl chloride and 0.004 parts of 2,7-diaminofluorene were uniformly mixed to obtain a mixture, and the mixture was added to the initial polymerization solution of step (1) (the addition rate of the mixture was 5 kg / h), and the temperature in the system was controlled to be 40° C. After the reaction was completed, calcium hydroxide was used for neutralization, and the pH was adjusted to 8.5 to finally obtain a highly heat-resistant meta-aramid polymer with a viscosity of 150 Po (25° C.), which was diluted with DMAC solvent to obtain a polymer dilution with a viscosity of 100 CP.
[0056] (3) The highly heat-resistant meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 30%) are transported to a precipitator at a mass ratio of 1:7 for high-speed shearing at a shear speed of 5000 rpm and a stock liquid gun diameter of 0.05 mm, and then countercurrent washing is performed to obtain the highly heat-resistant meta-aramid fiber precipitate.
[0057] Example 2
[0058] (1) Add 2 parts of m-phenylenediamine to 30 parts of N-methylpyrrolidone, control the temperature in the system to 5°C, add 1.8 parts of isophthaloyl chloride under nitrogen protection to carry out polymerization reaction, and obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride is 45 kg / h;
[0059] (2) 0.2 parts of isophthaloyl chloride and 0.002 parts of 2,7-bis(3-aminophenyl)fluorene were mixed uniformly to obtain a mixture, and the mixture was added to the initial polymerization solution of step (1) (the addition rate of the mixture was 10 kg / h). The temperature in the system was controlled to be 35° C. After the reaction was completed, sodium hydroxide was used for neutralization and the pH was adjusted to 8. Finally, a highly heat-resistant meta-aramid polymer with a viscosity of 120 Po (25° C.) was obtained. The polymer was diluted with DMAC solvent to obtain a polymer dilution with a viscosity of 100 CP.
[0060] (3) The highly heat-resistant meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 25%) are transported to a precipitator at a mass ratio of 1:8 for high-speed shearing at a shear speed of 6000 rpm and a stock liquid gun diameter of 0.06 mm, and then countercurrent washing is performed to obtain the highly heat-resistant meta-aramid fiber precipitate.
[0061] Example 3
[0062] (1) 2 parts of m-phenylenediamine were added to 30 parts of dimethylformamide, the temperature in the system was controlled to be 15°C, and 1.9 parts of isophthaloyl chloride were added under nitrogen protection to carry out polymerization reaction to obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride was 40 kg / h;
[0063] (2) 0.1 parts of isophthaloyl chloride and 0.005 parts of 9.9-dimethyl-2,7-bis(3-aminophenyl)fluorene were uniformly mixed to obtain a mixture, and the mixture was added to the initial polymerization solution of step (1) (the addition rate of the mixture was 15 kg / h), and the temperature in the system was controlled to be 20° C. After the reaction was completed, sodium hydroxide was used for neutralization, and the pH was adjusted to 8.5. Finally, a highly heat-resistant meta-aramid polymer with a viscosity of 100 Po (25° C.) was obtained, which was diluted with DMAC solvent to obtain a polymer dilution with a viscosity of 100 CP.
[0064] (3) The highly heat-resistant meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 45%) are transported to a precipitator at a mass ratio of 1:9 for high-speed shearing at a shear speed of 7000 rpm and a stock liquid gun diameter of 0.04 mm, and then countercurrent washing is performed to obtain the highly heat-resistant meta-aramid precipitated fibers.
[0065] Example 4
[0066] (1) 2 parts of m-phenylenediamine were added to 30 parts of dimethylacetamide, the temperature in the system was controlled to be 15°C, and 1.2 parts of isophthaloyl chloride were added under nitrogen protection to carry out polymerization reaction to obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride was 30 kg / h;
[0067] (2) 0.4 parts of isophthaloyl chloride and 0.004 parts of 2,7-diaminofluorene were mixed uniformly to obtain a mixture, and the mixture was added to the initial polymerization solution of step (1) (the addition rate of the mixture was 10 kg / h), and the temperature in the system was controlled to be 25° C. After the reaction was completed, calcium hydroxide was used for neutralization, and the pH was adjusted to 10 to finally obtain a highly heat-resistant meta-aramid polymer with a viscosity of 140 Po (25° C.), which was diluted with DMAC solvent to obtain a polymer dilution with a viscosity of 100 CP.
[0068] (3) The highly heat-resistant meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 35%) are transported to a precipitator at a mass ratio of 1:7 for high-speed shearing at a shear speed of 8000 rpm and a stock liquid gun diameter of 0.04 mm, and then countercurrent washing is performed to obtain the highly heat-resistant meta-aramid precipitated fibers.
[0069] Comparative Example 1
[0070] The meta-aramid fiber was prepared by the same method as in Example 1, except that the phenylenediamine monomer containing a fluorene structure was not added. The specific preparation process is as follows:
[0071] (1) 2 parts of m-phenylenediamine were added to 30 parts of dimethylacetamide, the temperature in the system was controlled to be 25°C, and 1.6 parts of isophthaloyl chloride were added under nitrogen protection to carry out polymerization reaction to obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride was 30 kg / h;
[0072] (2) 0.4 parts of isophthaloyl chloride was added to the initial polymerization solution of step (1) (the addition rate was 5 kg / h), and the temperature in the system was controlled to be 40°C. After the reaction was completed, calcium hydroxide was used for neutralization, and the pH was adjusted to 8.5. Finally, a viscosity of 150 Po (25°C) was obtained, which was meta-aramid polymer. The polymer was diluted with DMAC solvent to obtain a polymer dilution with a viscosity of 100 CP.
[0073] (3) The meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 30%) are transported to a precipitator at a mass ratio of 1:7 for high-speed shearing at a shear speed of 5000 rpm and a stock liquid gun diameter of 0.05 mm, and then countercurrent washing is performed to obtain the meta-aramid precipitated fibers.
[0074] Comparative Example 2
[0075] The conventional method is to add inorganic additives to the polymer to prepare heat-resistant meta-aramid fiber. The specific preparation process is as follows:
[0076] (1) 2 parts of m-phenylenediamine were added to 30 parts of dimethylacetamide, the temperature in the system was controlled to be 25°C, and 1.6 parts of isophthaloyl chloride were added under nitrogen protection to carry out polymerization reaction to obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride was 30 kg / h;
[0077] (2) 0.4 parts of isophthaloyl chloride was added to the initial polymerization solution of step (1) (the addition rate was 5 kg / h), and the temperature in the system was controlled to be 40°C. After the reaction was completed, calcium hydroxide was used for neutralization, and the pH was adjusted to 8.5. Finally, a viscosity of 150 Po (25°C) was obtained, which was meta-aramid polymer. The polymer was diluted with DMAC solvent to obtain a polymer dilution with a viscosity of 100 CP.
[0078] (3) Chlorine-based flame retardant powder (chlorinated paraffin) is added to the polymer and stirred to obtain a modified heat-resistant meta-aramid polymer.
[0079] (4) The modified heat-resistant meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 30%) were transported to a precipitator at a mass ratio of 1:7 for high-speed shearing at a shear speed of 5000 rpm and a stock gun diameter of 0.05 mm. The modified heat-resistant meta-aramid precipitated fibers were then prepared by countercurrent water washing. However, during the preparation process, the flame retardant powder agglomerated in the polymerization system, causing blockage in the precipitation equipment and the entire preparation process was not smooth.
[0080] Comparative Example 3
[0081] The meta-aramid fibrid was prepared by the same method as in Example 1, except that the mass ratio of the highly heat-resistant meta-aramid polymer to the DMAC aqueous solution in step (3) was 1:5, and the amount of the DMAC aqueous solution was lower than the amount specified in the present invention. The specific preparation process was as follows:
[0082] (1) 2 parts of m-phenylenediamine were added to 30 parts of dimethylacetamide, the temperature in the system was controlled to be 25°C, and 1.6 parts of isophthaloyl chloride were added under nitrogen protection to carry out polymerization reaction to obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride was 30 kg / h;
[0083] (2) 0.4 parts of isophthaloyl chloride and 0.004 parts of 2,7-diaminofluorene were uniformly mixed to obtain a mixture, and the mixture was added to the initial polymerization solution of step (1) (the addition rate of the mixture was 5 kg / h), and the temperature in the system was controlled to be 40° C. After the reaction was completed, calcium hydroxide was used for neutralization, and the pH was adjusted to 8.5 to finally obtain a highly heat-resistant meta-aramid polymer with a viscosity of 150 Po (25° C.), which was diluted with DMAC solvent to obtain a polymer dilution with a viscosity of 100 CP.
[0084] (3) The highly heat-resistant meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 30%) are transported to a precipitator at a mass ratio of 1:5 for high-speed shearing at a shear speed of 5000 rpm and a stock liquid gun diameter of 0.05 mm, and then countercurrent washing is performed to obtain the highly heat-resistant meta-aramid precipitated fibers.
[0085] Comparative Example 4
[0086] The meta-aramid fibrid was prepared by the same method as in Example 1, except that the mass ratio of the highly heat-resistant meta-aramid polymer to the DMAC aqueous solution in step (3) was 1:10, and the amount of the DMAC aqueous solution was higher than the amount specified in the present invention. The specific preparation process was as follows:
[0087] (1) 2 parts of m-phenylenediamine were added to 30 parts of dimethylacetamide, the temperature in the system was controlled to be 25°C, and 1.6 parts of isophthaloyl chloride were added under nitrogen protection to carry out polymerization reaction to obtain an initial polymerization solution, wherein the addition rate of isophthaloyl chloride was 30 kg / h;
[0088] (2) 0.4 parts of isophthaloyl chloride and 0.004 parts of 2,7-diaminofluorene were uniformly mixed to obtain a mixture, and the mixture was added to the initial polymerization solution of step (1) (the addition rate of the mixture was 5 kg / h), and the temperature in the system was controlled to be 40° C. After the reaction was completed, calcium hydroxide was used for neutralization, and the pH was adjusted to 8.5. Finally, a viscosity of 150 Po (25° C.) was obtained, which was a highly heat-resistant meta-aramid polymer. The polymer was diluted with DMAC to obtain a polymer dilution with a viscosity of 100 CP.
[0089] (3) The highly heat-resistant meta-aramid polymer dilution liquid and the DMAC aqueous solution (the mass concentration of DMAC in the DMAC aqueous solution is 30%) are transported to a precipitator at a mass ratio of 1:10 for high-speed shearing at a shear speed of 5000 rpm and a stock liquid gun diameter of 0.05 mm, and then countercurrent washing is performed to obtain the highly heat-resistant meta-aramid fiber precipitate.
[0090] The meta-aramid fibrids prepared in the above Examples 1-4 all comply with the national standard document GB / T 31889-2015. The meta-aramid fibrids prepared in the above Examples and Comparative Examples were subjected to performance tests, and the specific test methods are as follows:
[0091] (1) Aramid paper heat damage test method: The product is treated at 285°C and 2MPa, and then the tear strength test is performed according to the GB / T455-2002 test method.
[0092] (2) Limiting oxygen index test method: Test according to GB17591-2006 GB20286-2006 test method.
[0093] (3) Chloride ion test method: Test according to GB11896-89 test method.
[0094] (4) Fiber whiteness test method: Test according to GB / T 8940.2 test method.
[0095] (5) Test method for beating degree of fibrillation: Test according to the test method of GB / T 3332-2004.
[0096] The specific data are shown in Table 1.
[0097] Table 1 Relevant data of Examples 1-4 and Comparative Examples 1-4
[0098]
[0099] It can be seen from the experimental data of Examples 1 to 4 that by adopting the technical solution of the present invention, a highly heat-resistant meta-aramid fibrid product can be obtained in the fibrid process. Comparative Example 1 is a meta-aramid fibrid prepared by a conventional preparation method, and its heat loss resistance is 246cN, while the heat loss resistance of the meta-aramid fibrid prepared by the method of the present invention in Example 1 is only 45cN. By comparing the data of Example 1 with Comparative Example 1, it can be seen that by adopting the technical solution of the present invention, the heat loss resistance of the conventional meta-aramid fibrid can be improved by nearly 5 times.
[0100] Comparison of the data of Comparative Example 2 and Example 1 shows that the chloride ion content tested in Comparative Example 2 is greater than 3000ppm, which poses a risk of endangering human health, and the heat loss resistance of Comparative Example 2 is 103cN, which is significantly lower than the heat loss resistance of Example 1. This is because most of the halogen flame retardant powder is precipitated during the preparation of the fiber through molding, washing and other processes, which reduces the thermal stability of the product. The use of fluorene-containing diamine monomers to modify the molecular chain in the technical solution of the present invention is more conducive to the improvement of the thermal resistance of the fiber, and the effect of the fluorene-containing diamine monomer on the thermal stability of meta-aramid fiber is significantly better than that of halogen flame retardant powder; because the fluorene-based compound has good dielectric properties, mechanical properties, chemical resistance and moisture and heat resistance, the introduction of fluorene-based groups in the polymer molecular chain can effectively improve the thermal resistance of the polymer, and the fluorene structure is grafted into the polymer molecular chain in the form of a covalent bond, which will not cause functional attenuation due to the preparation process.
[0101] From the comparison of the experimental results of Comparative Examples 3-4 and Example 1, it can be seen that if the dosage ratio of the DMAC aqueous solution is too high or too low during the precipitation and forming process, the beating degree of the fibrid will be too high or too low, causing the stability of the downstream papermaking process to decrease, thereby affecting the heat resistance stability of the downstream products. Therefore, the precipitation and forming process conditions defined in the present invention are more conducive to obtaining high-heat-resistant meta-aramid fibrids with excellent performance. It provides raw materials with better performance for downstream product applications and improves the heat loss resistance of downstream products.
[0102] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0103] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A highly heat-resistant meta-aramid fiber, characterized in that: The meta-aramid fibrid contains at least one of the following structural polymers: ; The number average molecular weight of the meta-aramid fibrid is 150,000-220,000.
2. The method for preparing a highly heat-resistant meta-aramid fiber according to claim 1, characterized in that: The preparation method is: S1, m-phenylenediamine and isophthaloyl chloride are polymerized to obtain an initial polymerization solution; S2, mixing another portion of isophthaloyl chloride and the fluorene structure-containing phenylenediamine monomer to obtain a mixture, adding the mixture to the initial polymerization solution in step S1 to react, and after the reaction is completed, adjusting the pH to a weak alkaline state to obtain a highly heat-resistant meta-aramid polymer; S3, the high heat resistant meta-aramid polymer is subjected to a precipitation molding process to obtain the high heat resistant meta-aramid fibril; The precipitation forming process is as follows: the high heat resistant meta-aramid polymer is diluted with DMAC to obtain a polymer dilution with a mass concentration of 7-10wt%, the polymer dilution and the DMAC aqueous solution are transported to a precipitator for high-speed shearing, and then countercurrent washing is performed to obtain the high heat resistant meta-aramid fiber precipitation; The mass ratio of the high heat-resistant meta-aramid polymer to the DMAC aqueous solution is 1:(7-9), the mass concentration of DMAC in the DMAC aqueous solution is 25-45%; the speed of the high-speed shearing is 5000-8000rpm, and the diameter of the stock solution gun is 0.04-0.06mm.
3. The method for preparing a highly heat-resistant meta-aramid fiber according to claim 2, characterized in that: The fluorene structure-containing phenylenediamine monomer is any one of 2,7-diaminofluorene, 2.7-bis(3-aminophenyl)fluorene, and 9.9-dimethyl-2.7-bis(3-aminophenyl)fluorene.
4. The method for preparing a highly heat-resistant meta-aramid fiber according to claim 2, characterized in that: The molar ratio of the amount of m-phenylenediamine used in step S1 to the total amount of isophthaloyl chloride used in steps S1 and S2 is 1:(0.80-1.00); The molar ratio of the amount of the fluorene structure-containing phenylenediamine monomer used in step S2 to the amount of the m-phenylenediamine used in step S1 is (0.001-0.0025): 1; The amount of isophthaloyl chloride used in step S2 is 5% to 25% of the total mass of the isophthaloyl chloride in steps S1 and S2.
5. The method for preparing a highly heat-resistant meta-aramid fiber according to claim 2, characterized in that: The polymerization reaction process in step S1 is as follows: under the protection of inert gas, m-phenylenediamine is dissolved in a polar solvent, and then the isophthaloyl chloride is added, and the reaction temperature is controlled to be 5-25° C.; In step S2, the reaction is carried out under the protection of an inert gas, and the reaction temperature is controlled to be 20-40°C.
6. The method for preparing highly heat-resistant meta-aramid fibrid according to claim 5, characterized in that: In step S1, the addition rate of isophthaloyl chloride is 30-45 kg / h; in step S2, the addition rate of the mixture of isophthaloyl chloride and fluorene structure-containing phenylenediamine monomer is 5-15 kg / h.
7. The method for preparing highly heat-resistant meta-aramid fibrid according to claim 2, characterized in that: The mass concentration of the highly heat-resistant meta-aramid polymer is 15-20wt%, the viscosity at 25°C is 50-200 Po, and the polymer pH is 8-10.
8. The use of the highly heat-resistant meta-aramid fibrid according to claim 1 or the highly heat-resistant meta-aramid fibrid obtained by the preparation method according to any one of claims 2 to 7, characterized in that: The highly heat-resistant meta-aramid fibrid is applied to aramid paper.
Citation Information
Patent Citations
Anti-yellowing meta-aramid precipitation fiber as well as preparation method and application thereof
CN113789583A
Fluorene-containing diamine monomer, polyimide film and preparation method and application thereof
CN112778140A
Application of thermosetting polyimide in preparation of high-temperature-resistant resin-based composite material
CN114369243A